A comparison of the accuracy of two electronic hand hygiene monitoring systems. (13th August 2019) - Doll, Michelle E.; Masroor, Nadia; Cooper, Kaila; Trimmer, Trina; Pryor, Rachel; Auricchio, Joseph; Armstrong-Novak, Jo Dee; Stevens, Michael P.; Bearman, Gonzalo
Abstract: Interest in electronic hand hygiene monitoring systems (EHHMSs) is now widespread throughout the infection control community. We tested 2 types of EHHMS for accuracy. The type B EHHMS captured more HH events with superior accuracy. Hospitals considering an EHHMS should assess the technology's ability to accurately capture HH performance in the clinical workflow.